Penguatan Pendidikan Karakter di Pondok Pesantren Tahfizh Quran Hadits Rabbaniy Internasional Pekanbaru - Riau - Isran Bidin; Muhammad Isnaini; Mishart Mishart; Wismanto Wismanto; Khairul Amin (Departement of Mathematics Education, 2022)
Abstract This study aims to describe the Strengthening of Religious Character Education (PPK), nationalism, independence, mutual cooperation, and integrity at the Tahfizh Quran Hadith Rabbaniy International Islamic Boarding School Pekanbaru. The research approach used is a qualitative approach. The research subjects were the principal, 6 teachers and 6 students. Data collection techniques using interviews, observation, and documentation. The results of this study concluded: Strengthening religious character education at the tahfizh Quran Hadith Rabbani International Islamic Boarding School Pekanbaru is carried out integrated with several subjects that contain the Ministry of Religion and the Ministry of Education and Culture. Strengthening nationalism character education through Monday ceremonial activities and students also commemorate Teacher's Day with great wisdom. Strengthening mutual cooperation character education is realized in entrepreneurship learning related to agricultural and or fishing life skills in progress, students accompanied by class teachers cultivate plants around the school. Strengthening integrity character education can be seen in: 1) playing with friends regardless of physical condition, 2) being responsible for carrying out learning and in activities outside the classroom; 3) students buy food in the honesty canteen according to the prices listed; 4) students respect every member of the school through smiles, greetings, greetings, courtesy; 5) students do homework honestly; 6) students obey the class rules that have been made and mutually agreed upon (golden class).